Standardization of Epidemiological Surveillance of Group A Streptococcal Cellulitis . (15th September 2022) - Miller, Kate M; Lamagni, Theresa; Hay, Roderick; Cannon, Jeffrey W; Marks, Michael; Bowen, Asha C; Kaslow, David C; Cherian, Thomas; Seale, Anna C; Pickering, Janessa; Daw, Jessica N; Moore, Hannah C; et al.
Abstract: Cellulitis is an acute bacterial infection of the dermis and subcutaneous tissue usually found complicating a wound, ulcer, or dermatosis. This article provides guidelines for the surveillance of cellulitis. The primary objectives of cellulitis surveillance are to (1) monitor trends in rates of infection, (2) describe the demographic and clinical characteristics of patients with cellulitis, (3) estimate the frequency of complications, and (4) describe the risk factors associated with primary and recurrent cellulitis. This article includes case definitions for clinical cellulitis and group A streptococcal cellulitis, based on clinical and laboratory evidence, and case classifications for an initial and recurrent case. It is expected that surveillance for cellulitis will be for all-cause cellulitis, rather than specifically for Strep A cellulitis. Considerations of the type of surveillance are also presented, including identification of data sources and surveillance type. Minimal surveillance necessary for cellulitis is facility-based, passive surveillance. Prospective, active, facility-based surveillance is recommended for estimates of pathogen-specific cellulitis burden. Participant eligibility, surveillance population, and additional surveillance considerations such as active follow-up of cases, the use of International Classification of Disease diagnosis codes, and microbiological sampling of cases are discussed. Finally, the core data elements to be collected on case report forms are presented.